Social Networking Services-Based Communicative Care for Patients with Diabetes Mellitus in Korea - Kim, Hun-Sung; Jeong, Yoo Jin; Baik, Sun Jung; Yang, So Jung; Kim, Tong Min; Kim, Hyunah; Lee, Hyunyong; Lee, Seung-Hwan; Cho, Jae Hyoung; Choi, In-Young; Yoon, Kun-Ho (Applied Clinical Informatics, 2016)
Social networking services (SNS)-based online communities are good examples of improving quality of care by incorporating information technology into medicine. Therefore, we created an SNS-based community care webpage for communication among patients with diabetes mellitus (DM). We aimed to identify what diabetic patients wanted to know and were interested in by analyzing their posts and classified content in which users were interested.As opposed to the existing physician-focused health information websites, we built a patient-focused experience exchange website, “I love insulin (http://www.iloveinsulin.co.kr).” The DM communication webpage was divided into “My Web-Chart,” “My community-free board,” and “Life & Health.” The contents analysis targeted users’ postings, and replies were classified by theme from May 2012 to June 2013. The data included number of questions asked, answers, and question-to-answer (QA) ratio in each category.A total of 264 patients registered on the “I Love Insulin” website. The most frequent topic of posts classified as questions were about diabetes itself (23%), diet (22%), and glucose levels (19%). Conversely, most answers and information provided by users were about daily life with no relationship to diabetes mellitus (54%). While there were many questions about diet, there were very few answers (2%). Whereas there was much provision of knowledge about general DM, sharing diet information was rare. The ratios of answers to questions on diet (ratio=0.059, 1/17), glucose level (ratio=0.067, 1/15), insulin regulation (ratio=0.222, 2/9) and webpage (ratio=0.167, 1/6) were significantly low compared to DM itself (all p < 0.001).Patients in Korea with DM tend to have insufficient knowledge about diet and insulin regulation; continuously providing diet and insulin regulation information are desirable. It is hoped that the patients would be motivated to participate actively by “knowledge sharing.” Through this process, patients learn about their diseases not from the physicians but from among themselves.Citation: Kim H-S, Jeong YJ, Baik SJ, Yang SJ, Kim TM, Kim H, Lee H, Lee S-H, Cho JH, Choi I-Y, Yoon K-H. Social networking services-based communicative care for patients with diabetes mellitus.
Keywords: Diabetes mellitus; personal health records; communication; networks; home health; patient selfcare; home care and e-health; consumer health